Evaluating the Effectiveness of Cash Transfer Programs in Alleviating Poverty and Promoting Social Inclusion in Uzbekistan - Kuziyeva Gulnoza Rashidovna (European Science Publishing, 2023)
This research paper aims to assess the effectiveness of cash transfer programs in Uzbekistan in reducing poverty and promoting social inclusion. Cash transfer programs have emerged as an important social protection tool globally, and Uzbekistan has implemented several cash transfer programs targeting vulnerable populations. The study employs a mixed-methods approach, combining quantitative analysis of household survey data with qualitative interviews and case studies. The findings provide insights into the impact of cash transfer programs on poverty reduction, social inclusion, and the well-being of recipients. The research also examines the targeting mechanisms, delivery mechanisms, and policy implications of cash transfer programs in Uzbekistan.